Education on the Role of Learning Motivation in Improving Learning Achievement for Adolescents Assisted by Rumah Zakat Makassar - Faradillah Firdaus; Nurfitriany Fakhri; Kurniati Zainuddin; Muh. Nur Hidayat N; Tri Sulastri (PT FORMOSA CENDEKIA GLOBAL, 2022)
The obstacles experienced by students with changing the learning system to online during the Covid pandemic caused student learning motivation to decrease. Even though learning motivation is an important factor that can affect student learning performance in class. The low motivation to learn as expressed by youth assisted by partners is caused by several factors such as boring learning methods, facility constraints such as signal interference, quota limitations, or problems with the devices used, and students are easily distracted by games or social media during the learning process. This service activity aims to increase children's learning motivation by providing education to adolescents regarding the role of learning motivation and identifying things that can be a source of motivation in learning. The results of the dedication carried out show that there is a change in knowledge about the concept of motivation and student enthusiasm in learning.